Evaluasi Karakteristik Arus Lalu Lintas terhadap Kinerja Ruas Jalan Nasional - Paimin Paimin; Achmad Faisal; Suyitno Suyitno (Vokasi, 2017)
Growth and development of the city brings the impact of problems on the traffic flow system. In Putussibau City, National street which includes Jalan. D. I. Panjaitan – Jalan Kom. Yos. Sudarso – Jalan A. Yani is the easiest way to traffic congestion, the street is considered the most busy and dense. The purpose of this study is to identify characteristics level of performance street caused by vehicle traffic flow expressed degree of saturation the street, know the capacity of the street and predicting level of performance street for the following years so it can submit a plan of action and action plan program that can be done to handle traffic congestion problem in the street. Based on the projection degree of traffic flow saturation Jalan D. I. Panjaitan is known road performance still give services with degree of saturation < 1 until 2033 of 0,95, Jalan Kom. Yos. Sudarso until 2030 of 0,93 and Jalan A. Yani until 2026 of 0,99.